Entire solutions for the classical competitive Lotka–Volterra system with diffusion in the weak competition case. (August 2018) - Wang, Yang; Li, Xiong
Abstract: In this paper we are concerned with the construction of entire solutions for the classical competitive Lotka–Volterra system with diffusion in the weak competition. For this purpose we firstly analyze the asymptotic behavior of traveling front solutions for this system connecting the origin and the positive equilibrium. Then, by using two different ways to construct pairs of coupled super–sub solutions of this system, we obtain two different kinds of entire solutions. The construction of the first kind of entire solutions is based on these fronts, and their reflects as well as the solutions of the system without diffusion. One component of the solution starts from 0 at t ≈ − ∞, and as t goes to + ∞, the two components of the entire solution will eventually stay in a conformed region. Another kind of entire solutions is related to some traveling front solutions of scalar equations.